A software tool to understand the design of PIDA controllers. Issue 17 (2022) - Ferrari, Marco; Visioli, Antonio
Abstract: In this paper we present an interactive software tool that can be used to learn how to design a PIDA controller. After having selected a process model, the user can modify the controller parameters and evaluate the corresponding changes in the control system responses. In particular, the user can evaluate the set-point step response, the load disturbance step response and the noise rejection performance. Further, the frequency response of the system can also be analyzed. With such a tool, the physical meaning of the parameters can be better understood and this can facilitate the adoption of PIDA controllers as an alternative to PID controllers in industrial settings.